Methodological proposal of watershed management for sanitation, El Muerto watershed case - Mendoza-Guadarrama, Magaly (2017)
El Muerto stream, in the State of Mexico, presents pollution generated by human activities within its micro-watershed. The management of the contamination problem can be developed through the characteristics of water management. Because of this situation, the study of the water management process was undertaken to understand it from a five-core analysis: biophysical, socio-cultural, economic, technological and political-administrative, in order to find an alternative to simple visions regarding water use, and achieve a methodological management proposal.